PENGARUH KUALITAS PRODUK, PENETAPAN HARGA, PROMOSI DAN LOKASI TERHADAP KEPUTUSAN MENJADI MAHASISWA DI UNISRI SURAKARTA TAHUN AKADEMIK 2016/2017 - Fernando Rianto, Suprihatmi Sri Wardiningsih & Rahayu Triastity (Universitas Slamet Riyadi, 2017)
The purpose of this study to analyze the effect of product quality, pricing,promotion and location decision to become students. This study uses data qualitativeand quantitative. Data collection techniques by means of interviews, questionnaires,and observations. Data analysis technique used is multiple regression analysistechniques, the classic assumption test, t-test, the accuracy of the model and test thecoefficient of determination. The results of the analysis of determination coefficient ofR2 = 0,755, meaning that the magnitude of the effect of variable product quality,pricing, promotion and location decision to become students amounted to 75,5%. F testresults indicate that there is a positive and significant influence product quality decisionto become students. Pricing positive and significant impact to the decision being astudent. Promotion of positive and significant impact to the decision being a student.The location is negative and significant effect on decision become students.Keywords: product quality, pricing, promotion, location, decisions become a student